Paediatric supracondylar humeral fractures: The effect of the surgical specialty on the outcomes. (February 2019) - Saarinen, A. J.; Helenius, I.
Abstract: Purpose: The effect of surgical specialty on the outcomes of paediatric patients treated for displaced supracondylar humeral fractures remains unclear. The results of residents, paediatric surgeons and orthopaedic surgeons were compared. Methods: A retrospective review of 108 children (0 to 16 years) treated for displaced humeral supracondylar fractures (Gartland II or III) requiring closed or open reduction under general anaesthesia were included. The patient charts and radiographs were evaluated to identify type, grade and neurovascular complications. Operative performance (operative time, quality of reduction, need for open reduction, complications) of residents, paediatric surgeons and orthopaedic surgeons were evaluated. Results: Residents used a crossed pin configuration for patients in 25/25 (100%), paediatric surgeons in 25/32 (78%) and orthopaedic surgeons in 33/33 (100%) (p = 0.0011). Loss of reduction was present in one patient treated with crossed pins, in two with lateral pins and in two without Kirschner-wires (p = 0.0034). The risk ratio of an unacceptable reduction was 4.0 (95% confidence interval (CI) 0.90 to 18, p = 0.070) for residents and 6.6 (95% CI 1.6 to 27, p = 0.0082) for paediatric surgeons as compared with orthopaedic surgeons. Complications were present in 37% of patients (11/30) for residents, 55% (24/44) for paediatric surgeons and 15% (5/34) for orthopaedic surgeons (p = 0.0013). Conclusion: We found statistically significant differences in the incidence of unacceptable reduction, complications and the usage of crossed pin configuration between the surgical specialties. Patients would benefit from the practice of assigning the operative treatment of displaced supracondylar fractures to orthopaedic surgeons. Level of evidence: Level III